Peran strategis kelompok sadar wisata dalam pengembangan Wisata Embung Banyu Langit di Desa Suka Maju - Farhan Mustaqim Al-Qadhri; Ahmad Hidayah; Novita Surya Ningsih; Zulkifli Abdullah (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the role of the Kelompok Sadar Wisata (POKDARWIS) in the development of Embung Banyu Langit tourism in Suka Maju Village, Kongbeng District, East Kutai. This research used qualitative method with data collection techniques including in-dept interviews, participatory observation, and document analysis. Data analysis is conducted descriptively and qualitatively to illustrate the role of POKDARWIS in managing, promoting and empowering the local community to ensure the sustainable development of Embung Banyu Langit tourism. The result show that POKDARWIS of Suka Maju Village plays a significant role as a facilitator, motivator, initiator and manager in tourism development. Supporting factors include the village’s tourism attraction, government support, and active community participation. Based on these findings, this study recomendeds increased support from the government and stakeholders to strengthen the capacity and role of POKDARWIS in Suka Maju Village to achieve sustainable and inclusive tourism development.